2017
DOI: 10.1111/jgs.14889
|View full text |Cite
|
Sign up to set email alerts
|

Home‐ and Community‐Based Occupational Therapy Improves Functioning in Frail Older People: A Systematic Review

Abstract: There is strong evidence that occupational therapy improves functioning in community-dwelling physically frail older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 30 publications
(129 reference statements)
1
56
0
7
Order By: Relevance
“…Benefits from such interventions in elderly populations have been described broadly. 45 48 A systematic review of home- and community-based occupational therapy from 2017 concluded that there is strong evidence that occupational therapy improves the ability to perform daily activities in elderly. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Benefits from such interventions in elderly populations have been described broadly. 45 48 A systematic review of home- and community-based occupational therapy from 2017 concluded that there is strong evidence that occupational therapy improves the ability to perform daily activities in elderly. 45 …”
Section: Discussionmentioning
confidence: 99%
“…However, no study has been conducted in our national literature. Actually, most of the studies have been conducted on geriatric population (De Coninck, Bekkering, Bouckaert et al, 2017;Stark, Keglovits, Arbesman et al, 2017;Kamei, Kajii, Yamamoto et al, 2015;Matsuda et al, 2011). Whiteneck et al (2004) reported that the five most important environmental barriers for subjects with SCI: natural environment, transportation, domestic assistance, the availability of healthcare, and governmental policies.…”
Section: Discussionmentioning
confidence: 99%
“…Podría pensarse que este número es bajo en proporción, no obstante, dicha valoración debe hacerse con responsabilidad a la luz de la evidencia disponible. Como ejemplo, esta revisión constató que el problema de salud N°36 "Órtesis (o ayudas técnicas) para personas de 65 años y más" no incorpora la acción del terapeuta ocupacional, siendo ésta un componente de intervención frecuente en la acción y formación profesional, y en la que existe evidencia creciente de su efectividad a partir de ensayos controlados aleatorizados, revisiones sistemáticas y estudios de costo efectividad (Clark et al, 2012;De Coninck et al, 2017;Zingmark, Nilsson, Norström, Sahlén & Lindholm, 2017).…”
Section: Discussionunclassified